Mapping the digital landscape: A bibliometric analysis of digital ecosystem research - Arne Jeppe; Tim Bree; Erik Karger; Heike Proff; Frederik Ahlemann (Digital Business)
Digital ecosystems have become a central paradigm for understanding the complex, interconnected networks that characterize the modern digital landscape. However, the rapid growth and interdisciplinary nature of this research present challenges for scholars seeking to grasp its intellectual structure and future trajectory. This study addresses this gap by conducting a comprehensive bibliometric analysis of 1974 publications retrieved from the Scopus database. We map the intellectual structure of the field, identify key research themes, and uncover influential contributors and publications. Our analysis reveals five major thematic clusters: (1) Digital Transformation and Economy, (2) Emerging Technologies and Learning Systems, (3) Foundational Technologies and Semantic Architecture, (4) Human and Social Interaction in Digital Spaces, and (5) Business Strategy and Innovation. Building on this analysis, we outline a detailed agenda for future research, highlighting critical needs in areas such as adaptive governance, social and environmental sustainability, the security of digital infrastructures, and the human-centric application of AI in domains like healthcare. This study provides the first large-scale, holistic overview of digital ecosystem research, offering a robust foundation for future investigations and informing strategic decisions for researchers, practitioners, and policymakers.